Penguatan Regulasi Anti-SLAPP Dalam Perlindungan Hukum Aktivis Lingkungan di Indonesia - Sukmadewi, Yudhitiya Dyah; Endah Pujiastuti; Tri Mulyani; Supriyadi Supriyadi; Kartika Widya Utama (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the urgency of strengthening Anti-SLAPP regulation in the legal protection of environmental activists in Indonesia and to evaluate the effectiveness of its regulation based on Lawrence M. Friedman’s legal system framework. This study is motivated by the ineffectiveness of Anti-SLAPP regulation in protecting environmental activists from criminalization, while previous studies have not provided a comprehensive analysis integrating legal substance, law enforcement structure, and legal culture as a unified system. The study employs normative legal research using statutory and conceptual approaches, based on secondary data consisting of primary and secondary legal materials analyzed qualitatively through deductive reasoning. The findings indicate that the ineffectiveness of Anti-SLAPP regulation is caused by the lack of operational clarity in Article 66 of the Environmental Protection and Management Law (legal substance), law enforcement interpretations that are inconsistent with the principles of lex specialis and ultimum remedium (legal structure), and low levels of public participation and legal awareness (legal culture). This study offers novelty in the form of an evaluation framework for Anti-SLAPP effectiveness based on Friedman’s legal system, which assesses the legal system systematically while formulating the need to revise the Environmental Protection and Management Law to ensure that legal protection becomes more operational and implementable. Penelitian ini bertujuan menganalisis urgensi penguatan regulasi Anti-SLAPP dalam perlindungan hukum aktivis lingkungan di Indonesia serta mengevaluasi efektivitas pengaturannya berdasarkan sistem hukum Lawrence M. Friedman. Kajian ini dilatarbelakangi oleh belum efektifnya pengaturan Anti-SLAPP dalam melindungi aktivis lingkungan dari kriminalisasi, sementara penelitian terdahulu belum memberikan analisis komprehensif yang mengintegrasikan substansi hukum, struktur penegakan hukum, dan kultur hukum sebagai satu sistem. Penelitian menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual, berbasis data sekunder berupa bahan hukum primer dan sekunder yang dianalisis secara kualitatif melalui penalaran deduktif. Hasil penelitian menunjukkan bahwa ketidakefektifan regulasi Anti-SLAPP disebabkan oleh ketidakjelasan operasional Pasal 66 UUPPLH (substansi), penafsiran APH yang tidak konsisten dengan asas lex specialis dan ultimum remedium (struktur), serta rendahnya partisipasi dan kesadaran hukum masyarakat (kultur). Penelitian ini menawarkan kebaruan berupa kerangka evaluasi efektivitas Anti-SLAPP berbasis sistem hukum Friedman yang menilai hukum secara sistemik sekaligus merumuskan kebutuhan revisi UUPPLH agar perlindungan hukum lebih operasional dan implementatif.